Stable field emission from hydrothermally grown ZnO nanotubes - Wei, A. (2011)
Zinc oxide nanotube arrays were prepared by hydrothermal reaction in ammonia and zinc chloride solutions, and the field emission properties were tested. The turn-on field of the field emission was extrapolated to be about 7.0 V/μm at a current density of 0.1 μA/cm2. Meanwhile, the emission current densities reached 1 mA/cm2 at a bias field of 17.8 V/μm. The field enhancement factor β was estimated to be 910. The field emission of the zinc oxide nanotubes showed good stability. The variation of emission current density was less than 10% during a 24 h test under a field of 15 V/μm.